Factors Affecting Employee Performance: Analysis of Work-Life Balance, Competence, Employee Welfare, and Career Development - Liana, Esti; Hartono, Hartono (Green Publisher, 2024)
The purpose of this literature research is expected to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of human resource management. The literature review research article on factors that influence employee performance: analysis of work life balance, competence, employee welfare and career development is a scientific literature article in the scope of human resource management science. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or conduct a review of relevant previous articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is sourced from academic online media such as the Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Emerald, Sage, WoS, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. The results of this literature review article are: 1) Work Life Balance affects Employee Performance; 2) Competence affects Employee Performance; 3) Employee Welfare affects Employee Performance; and 4) Career Development affects Employee Performance.